2016
DOI: 10.1038/tpj.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

New polymorphisms associated with response to anti-TNF drugs in patients with moderate-to-severe plaque psoriasis

Abstract: Anti-tumor necrosis factor (anti-TNF) drugs are effective against psoriasis, although 20-30% of patients are nonresponders. Few pharmacogenomic studies have been performed to predict the response to anti-TNF drugs in psoriasis. We studied 173 polymorphisms to establish an association with the response to anti-TNF drugs in patients with moderate-to-severe plaque psoriasis (N=144). We evaluated the response using PASI75 at 3, 6 and 12 months. The results of the multivariate analysis showed an association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 67%
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 67%
“…The field of pharmacogenetics is growing rapidly. Already, new papers have been published following the end date of our literature search, discovering response‐associated polymorphisms in genes not described previously for psoriasis, such as CD84 , PGLYR4 , ZNF816A , CTNNA2 , MAP3K1 and HTR2A …”
Section: Discussionmentioning
confidence: 99%
“…The SNP þ489 A/ A genotype was associated with a response to adalimumab in patients with psoriatic arthritis (Murdaca et al, 2014). Recently, investigators found an association of six SNPs involved in immune response, keratinocyte differentiation, and response to anti-TNF therapies for patients with moderate to severe plaque psoriasis (Prieto-Pérez et al, 2016). On the other hand, one study found that SNP data did not meaningfully contribute to the prediction of treatment response in patients with rheumatoid arthritis taking anti-TNFs (Sieberts et al, 2016).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%